De l’engagement des acteurs locaux dans le processus de l’intégration des pygmées au système éducationnel en chefferies et secteur du Territoire de Wamba en République Démocratique du Congo. - Félix-Amand FUFULAFU ZANIWE (IJRDO- Journal of Educational Research, 2021)
This paper focuses on the social and economic activities of the integration of pygmies in the Democratic Republic of Congo and more specifically those of the Territory of Wamba in the Province of Haut-Uélé. The pygmies are people who live in villages and in groups. They are managed on a daily basis for the customary power, according to the law of the contry, the commitment of development actors in the field of pygmy education in order to raise their level of education is observed through the process that is carried out in favor of these peoples. The experience of the chiefdoms and sector of the Territory of Wamba makes it possible to understand the dynamism which is realized in this sector considered to be one of the main strategies of the integration of the pygmies. Since it allows on the one hand increasing the level of knowledge of the pygmies thanks to the diversity of the teaching which can be given and on the other hand, it makes it possible to bring together the school population as well as the parents in research the solutions group on issues related to their children’s schooling.